EFEKTIVITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY PADA BANK SYARIAH MANDIRI DI KOTA AMBON - Maratun Shalihah; Mahwa Soraya Tuasikal (IAIN Ambon, 2018)
Bank Syariah Mandiri in Ambon City as part of a public company has social responsibility through the implementation of Corporate Social Responsibility (CSR) to help the community. The implementation of the CSR program at BSM in Ambon City aims to create a brand image and brand reputation as well as to create innovation. Without leaving the view of Beyond compliance or compliance plus which is a sincere encouragement to help in the implementation of CSR, in general the form of CSR programs is philantropy. The effectiveness of the CSR program on BSM from effectiveness aspects (benefits) and relevance aspects (suitability) received positive appreciation from the community because this aspect was felt to be able to provide benefits to the communities in the company's operating area.